1998
DOI: 10.1074/jbc.273.22.13552
|View full text |Cite
|
Sign up to set email alerts
|

Isoforms of Hepatocyte Nuclear Factor-6 Differ in DNA-binding Properties, Contain a Bifunctional Homeodomain, and Define the New ONECUT Class of Homeodomain Proteins

Abstract: Hepatocyte nuclear factor-6 (HNF-6) contains a single cut domain and a homeodomain characterized by a phenylalanine at position 48 and a methionine at position 50. We describe here two isoforms of HNF-6 which differ by the linker that separates these domains. Both isoforms stimulated transcription. The affinity of HNF-6␣ and HNF-6␤ for DNA differed, depending on the target sequence. Binding of HNF-6 to DNA involved the cut domain and the homeodomain, but the latter was not required for binding to a subset of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
117
0
4

Year Published

2001
2001
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 96 publications
(130 citation statements)
references
References 43 publications
(51 reference statements)
9
117
0
4
Order By: Relevance
“…The molecular dissection of OC1 revealed that the cut domain and the homeodomain act together to determine DNA-binding affinity, specificity and transactivation. 20 The sequence conservation in these domains among the three paralogues suggests that OC2 binds a similar DNA consensus sequence to OC1. Indeed, many of the OC1 targets are also recognized by OC2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The molecular dissection of OC1 revealed that the cut domain and the homeodomain act together to determine DNA-binding affinity, specificity and transactivation. 20 The sequence conservation in these domains among the three paralogues suggests that OC2 binds a similar DNA consensus sequence to OC1. Indeed, many of the OC1 targets are also recognized by OC2.…”
Section: Resultsmentioning
confidence: 99%
“…The alignment of these sequences revealed the consensus, 5 0 -AATCG(A)ATA(C)-3 0 (Figure 4b), which overlapped significantly with those of the cut domain of human CDP (5 0 -ATCGAT-3 0 ) and OC1 (5 0 -ATCAAT-3 0 ). 20,22 Based on the consensus-binding sequence of OC2, we searched for candidate target genes encoding proteins related to Th1 function by checking the genome sequences of the promoter region. We found tandem repeats of the consensus sequence 5 0 upstream of the human T-bet gene, 5 0 -ATCAATAAAGATCGAT-3 0 , in the region from À490 to À475 (the consensus sequences are underlined and designated as 'site 1' and 'site 2', Figure S1) were mutated in the reporter containing OC2 promoter (À451 to þ 124) and the reporter activities of each construct, as well as the wild-type (top) and OC2 promoter (À347 to þ 124, bottom), were examined in the presence or absence of T-bet in COS7 cells.…”
Section: Resultsmentioning
confidence: 99%
“…pECE-HNF6α, pECE-HNF6β and pXJ42-OC2 have been described [12,13,14]. The pXP2-GKS1 firefly luciferase reporter vector contains the hepatic promoter of the mouse glucokinase gene (-987 to +19) cloned in the SacI and BglII sites of pXP2.…”
Section: Methodsmentioning
confidence: 99%
“…This fragment includes the distal (-7613 to -7622) HNF-6 binding site. The internal control vector pRL-138 coding Renilla luciferase contains the pfk-2 promoter (-138 to +86) cloned in pRLnull (Promega, Leiden, The Netherlands) [13].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation